Effective Learning Strategies: The Role of Teachers in Enhancing Junior High School Students' Narrative Writing Skills through Differentiated Instruction - Husnul Khotimah; Ninuk Lustyantie; Fathiaty Murtadho (Universitas Islam Negeri Palopo, 2025)
The ability to write narrative texts is a fundamental skill in English language education, especially at the Junior High School (JHS) level. However, many students face challenges in organizing ideas and writing narratives that are both structured and engaging. Differentiated Instruction (DI) offers a solution by tailoring teaching to meet the individual needs of students. This study aims to explore the implementation of DI in teaching narrative writing at JHS, particularly in English language classes. The research employed a qualitative descriptive approach with a case study design, focusing on two experienced English teachers and their students. The results indicated that DI significantly improved students' writing skills, particularly in organizing ideas, structuring texts, and enhancing creativity in character development and plot construction. Students in classes using DI showed increased motivation, confidence, and better use of language. Despite challenges such as diverse student abilities and limited resources, DI was found to positively impact students' writing outcomes. The study concludes that DI is an effective method for improving narrative writing skills in English classes at JHS, offering a flexible and student-centered approach to teaching.